1988
DOI: 10.1055/s-2008-1050274
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonia bulbi und Gonadotropine bei myotonischer Dystrophie

Abstract: Patients with myotonic dystrophy show ocular hypotony associated with primary hypogonadism and a secondary increase in the gonadotropins FSH and LH. By examining ten patients (nine men, one woman) with myotonic dystrophy and determining serum FSH and LH concentrations by radioimmunoassay, the authors tried to evaluate whether the decrease in intraocular pressure (IOP) seen in myotonic dystrophy might be related to increase levels of gonadotropins. The IOP of the patients with myotonic dystrophy (mean 10.6 mm H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Behrens et al [2] showed that apamin-sensitive K + channel disorder leads to the occurrence of myotonia in DM. Red blood cells, monocytes, fibroblasts, and lymphocytes have been cultured in vitro to clarify the mechanisms of disregulated signal transduction [13,14,20,22,23,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Behrens et al [2] showed that apamin-sensitive K + channel disorder leads to the occurrence of myotonia in DM. Red blood cells, monocytes, fibroblasts, and lymphocytes have been cultured in vitro to clarify the mechanisms of disregulated signal transduction [13,14,20,22,23,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Die Katarakt und die Ptosis gehçren zu den häufigsten Manifestationen, die auch bei unserer Patientin diagnostiziert wurden. Seltener treten eine externe Ophthalmoplegie, eine Licht-Nah-Dissoziation der Pupillen, eine Retinopathie mit Pigmentveränderungen der Netzhaut sowie eine Hypotonia bulbi auf [3,5,18,20,23,25,29]. Bei unserer Patientin beobachteten wir ebenfalls relativ niedrige Augeninnendruckwerte bei zwei nachfolgenden Messungen.…”
Section: Zusammenfassung !unclassified
“…andere okuläre Korrelate gefunden [13]. Meist sind es die Linsentrübungen, welche die Patienten den Augenarzt aufsuchen lassen [23]. Eine sternfçrmige, hintere subkapsuläre Katarakt stellt oft eine differenzialdiagnostische Herausforderung dar, wenn sie mit multisystemischen Assoziationen, vor allem Muskelschwäche und -atrophien auftritt [3].…”
Section: Zusammenfassung !unclassified